Mirroring its British Masters: State and Outsourced Terrorism against the Maoist Insurgency - Costa Lima, Felipe (Conjuntura Austral, 2022)
The Indian state has been adopting controversial policies for countering the Maoist insurgency. Even worse, this behaviour seems to mirror British colonial attitudes against India’s population at some level. Consequently, this article attempts to understand this probable ‘paradoxical’ conduct. With the support of the post-structuralist theory, I discuss state and outsourced terrorist practices of the Indian state apparatus against this insurgency. To reach this goal, first, I try to explicate the concept of state terrorism and its application in India. Then, I analyse the historical development of the Maoist movement and India’s concrete policies of state and outsourced terrorism against this counter-hegemonic movement. I believe the British Raj’s colonial practices have had a deep dialectical influence on India’s state apparatus and major political parties to date. So, this inquiry may clarify the persistence of colonial practices within India.